gonarthrosis; therapy; Karmolis gel. - B. V. Zavodovsky; E. E. Mozgovaya; Yu. R. Akhverdyan; I. A. Zborovskaya (Научно-практическая ревматология, 2014)
Objective: to evaluate the efficacy, tolerance, and safety of Carmolis topical gel in patients with gonarthrosis. Subjects and methods. The investigation enrolled 60 patients with knee osteoarthrosis (OA) who were divided into two groups: 1) 40 patients received Carmolis topical gel in addition to nonsteroidal anti-inflammatory drugs (NSAIDs); 2) 20 patients took NSAIDS only (a control group). The treatment duration was 2 weeks. In both groups, therapeutic effectiveness was evaluated from changes in the WOMAC index, pain intensity at rest and during movement by the visual analog scale (VAS). The disease activity was also assessed by a physician and a patient (a Likert scale), local swelling and hyperthermia of the affected joint, the efficiency of treatment, and daily needs for NSAIDs were deter- mined. Results. The performed treatment in both patent groups showed positive clinical changes. Combination therapy involving Carmolis gel displayed greater reductions in WOMAC pain and resting and movement pain than in the con- trol group (as assessed by VAS). On completion of the investigation, considerable improvement was, in the physicians' opinion, noted in 38 (95%) patients using Carmolis, which coincided with self-evaluations of the patients. During Carmolis application, the starting dose of NSAIDs could be reduced in 18 (45%) patients. Adverse reactions occurred infrequently and required no therapy discontinuation. Conclusion. Carmolis topical gel is effective in relieving clinical symptoms in patients with gonarthrosis, well tolerated, and safe, which can recommend its use in the combination treatment of knee OA.